Case Report: Cyanide in a Fatal Herbal Drink: An Exhumation Case Study - Nurhantari, Yudha; Pidada, Ida Bagus Gede Surya Putra; Widagdo, Hendro; Suhartini, Suhartini; Riyantingtyas, Lipur (International Journal of Medical Toxicology and Forensic Medicine, 2017)
Background: Traditional herbal drink, Jamu, is popular among Javanese. This paper reports two cases of death after taking a slimming Jamu. Interestingly, an illegal love affair was involved in this the case too. Case Report: The first victim (victim 1), a female, rapidly convulsed and died after taking a slimming Jamu drink. However, her brother (victim 2), after tasting just a small amount of that Jamu, rapidly became convulsive and unconscious. Although, he was immediately brought to hospital, he died before receiving any treatment. Because the death was unnatural, he was sent to the Department of Forensic Medicine for investigation. His sister was buried without any medico-legal examination, but later on the exhumation was performed. In autopsy, the victim 1 was found pregnant. Both victims had no injury on their bodies. Evidence of cyanide was positive in tissue samples, but negative in the control sample (soil). Conclusion: Both victims had the same cause of death, which was cyanide poisoning. The manner of death was suspected as homicide.